Adsorption of bio-organic eco-corona molecules reduces the toxic response to metallic nanoparticles in Daphnia magna - Mikael T. Ekvall (Nature Portfolio, 2021)
Abstract As the use of engineered nanomaterials increases, so does the risk of them spreading to natural ecosystems. Hitherto, knowledge regarding the toxic properties of nanoparticles (NP’s) and their potential interactions with natural bio-organic molecules adsorbed to them, and thereby forming surface coronas, is limited. However, we show here that the toxic effect of NPs of tungsten carbide cobalt (WC–Co) and cobalt (Co) on the crustacean Daphnia magna is postponed in the presence of natural biological degradation products (eco-corona biomolecules). For Daphnia exposed to WC–Co NPs the survival time increased with 20–25% and for Co NPs with 30–47% after mixing the particles with a solution of eco-corona biomolecules before exposure. This suggests that an eco-corona, composed of biomolecules always present in natural ecosystems, reduces the toxic potency of both studied NPs. Further, the eco-coronas did not affect the particle uptake, suggesting that the reduction in toxicity was related to the particle-organism interaction after eco-corona formation. In a broader context, this implies that although the increasing use and production of NPs may constitute a novel, global environmental threat, the acute toxicity and long-term effects of some NPs will, at least under certain conditions, be reduced as they enter natural ecosystems.